2008
DOI: 10.1210/en.2008-0512
|View full text |Cite
|
Sign up to set email alerts
|

Progestin Signaling through an Olfactory G Protein and Membrane Progestin Receptor-α in Atlantic Croaker Sperm: Potential Role in Induction of Sperm Hypermotility

Abstract: Progestin stimulation of sperm hypermotility remains poorly understood despite having been described in numerous vertebrate species. We show here that progestin stimulation of sperm hypermotility in a teleost, the Atlantic croaker (Micropogonias undulatus) is associated with activation of an olfactory G protein (Golf). Furthermore, we provide evidence that this progestin action is mediated by membrane progestin receptor-alpha (mPRalpha). Golf was identified in croaker sperm membranes and was specifically activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
70
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 57 publications
6
70
0
Order By: Relevance
“…During the reproductive cycle in mammals, fish and frogs mPRs, like mPRα, mediate the induction of oocyte maturation and sperm motility, which could involve the activation of a G-protein, upon binding of progestins (34,37,41,45). An immunological response linked to reproduction is the up-regulation of the leukemia inhibitory factor by progesterone, which is essential for the implantation and development of the embryo and inhibits several macrophage functions (25).…”
Section: Discussionmentioning
confidence: 99%
“…During the reproductive cycle in mammals, fish and frogs mPRs, like mPRα, mediate the induction of oocyte maturation and sperm motility, which could involve the activation of a G-protein, upon binding of progestins (34,37,41,45). An immunological response linked to reproduction is the up-regulation of the leukemia inhibitory factor by progesterone, which is essential for the implantation and development of the embryo and inhibits several macrophage functions (25).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that fish sperm with low motility expressed decreased mPRa protein in their sperm membranes (Tubbs and Thomas 2009). Immunocytochemistry of whole croaker spermatozoa with anti-mPRa antibody suggested the potential role of the receptor in mediating the maturation-inducing steroid stimulation of sperm motility .…”
Section: Mpra Expression and Mouse Spermatogenesismentioning
confidence: 98%
“…The mPR␣ subtype is ubiquitously expressed in vertebrate tissues and is the intermediary in a variety of nongenomic progesterone actions in fishes, including induction of oocyte maturation and sperm motility (68,74) and inhibition of granulosa cell apoptosis (13). The mPR␣ has also been implicated in progesterone modulation of gonadotropin-releasing hormone (GnRH) neuronal, T lymphocyte, breast cancer cell, and myometrial cell functions in mammalian cells (10,11,23,36,59).…”
mentioning
confidence: 99%